Characterization of Protease Soluble Collagen (PSC) From Milkfish Scales (Chanos chanos) - Nia Lutfiana Lutfiana; Suharti Suharti; Evi Susanti (Chemistry Department, The University of Brawijaya, 2019)
The aim of this study was to characterize protease soluble collagen (PSC) obtained from milkfish scales, extraction using protease from proteolytic bacteria HTcUM7.1 isolate. The characterization included Fourier Transform Infra Red (FT-IR) spectra, Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS-PAGE) profile, Field Emission Scanning Electron Microscopy (FESEM), denaturation temperature by Differential Scanning Calorimetric (DSC) and solubility. The resulting PSC from milkfish scales has white color, fiber with a length of about 20-60 µm, FTIR spectra and SDS-PAGE profile showed that PSC was collagen Type I and denaturation temperature was 145.48 °C, with maximum solubility at pH 1-3 and 1-2 % NaCl. Its high denaturation temperature value allows the collagen to be applied in the fields of medicines and cosmetics.